Precise measurement of the scintillation decay constant of the ZnWO4 crystal. (21st October 2021) - Shibata, M; Sekiya, H; Ichimura, K
Abstract: The scintillation decay time constant of a ZnWO4 crystal irradiated with α-particles from 241 Am was precisely investigated, and was found to depend on the incident direction of the α-particles on the crystal. The longest decay time constant (24.3 ± 0.6 μs) was obtained on the surface perpendicular to the b -axis of the crystal (surface B). On surfaces A and C, the decay constants were 20.0 and 21.3 ± 0.2 μs, respectively. The scintillation yield of ZnWO4 was also anisotropic and depended on the incident direction of the heavy particles. The maximum yield was achieved on surface B, suggesting a correlation between the light yield and the scintillation decay time constant of ZnWO4 crystals.